ECMWF Lightning Forecast in Mainland Portugal during Four Fire Seasons - Cátia Campos; Flavio T. Couto; Filippe L. M. Santos; João Rio; Teresa Ferreira; Rui Salgado (Atmosphere, 2024)
The study evaluated the ECMWF model ability in forecasting lightning in Portugal during four fire seasons (2019–2022). The evaluation was made based on lightning data from the national lightning detector network, which was aggregated into resolutions of 0.5° and 1° over 3 h periods and analyzed from statistical indices using two contingency tables. The results showed that the model overestimates the lightning occurrence, with a BIAS greater than 1, with a success rate of 57.7% (49%) for a horizontal resolution of 1° (0.5°). The objective analysis was complemented by the spatial lightning distribution analysis, which indicated a time lag between the two data, i.e., the model started predicting lightning before its occurrence and finished the prediction earlier. Furthermore, such analysis revealed the lightning distribution being consistent with some weather patterns. The findings of this study provide insights into the applicability of the ECMWF lightning forecast data in the context of forecasting natural forest fires in Portugal.